Genetics techniques for Thermococcus kodakarensis - Travis H. Hileman; Thomas James Santangelo (Frontiers in Microbiology, 2012)
Thermococcus kodakarensis (T.k.) has emerged as a premier model system for studies of archaeal biochemistry, genetics, and hyperthermophily. This prominence is derived largely from the natural competence of T.k. and the comprehensive, rapid, and facile techniques available for manipulation of the T.k. genome. These genetic capacities are complemented by robust planktonic growth, simple selections and screens, defined in vitro transcription and translation systems, replicative expression plasmids, in vivo reporter constructs, and an ever-expanding knowledge of the regulatory mechanisms underlying T.k. metabolism. Here we review the existing techniques for genetic and biochemical manipulation of T.k. We also introduce a universal platform to generate the first comprehensive deletion and epitope/affinity-tagged archaeal strain libraries.